Evidentiality and lexicalisation in the Spanish phraseological system: A study of the idiom a fe mía (and its variants). (April 2015) - Torrent, Aina
This work addresses the relation among the semantic-pragmatic categories of evidentiality, epistemicity and intensification based on a study of the discursive use of certain Spanish idiomatic phraseological units. The first part offers an introduction to some theoretical aspects, while the second part analyses the usage of the idiom a fe que . Two important theses that are defended in this article are as follows: (a) evidentiality has played an important role in the process of lexicalisation and grammaticalisation of a number of idiomatic phraseological units and (b) some evidential expressions display the existence of close relationships among evidentiality, epistemicity and intensification.